Webster's new world dictionary of computer terms : Completely revised & updated. (New York : Prentice-Hall, 1988)
Webster's new world dictionary of computer terms, third edition is a collection of more than 4,500 computer terms that focus on those topics of interest to computer users.
Keywords: DICTIONARY